The Flag as a Symbol and Vision of Peace, Democracy, and Nation-Building - Joan Davison; Jesenko Tešan (RIRAI Publisher, 2024)
The design of the flag of Bosnia and Herzegovina (B&H) illustrates both the objectives and limitations of intentional design’s role in national healing and state building following violent conflict. The architecture and design of public buildings, spaces, and symbols can facilitate sociability or reinforce segregation and hostility. This analysis contends that design, especially of public symbols intended to evoke emotions and unity, can facilitate healing. Yet in this case, the flag's design ignores the conflict, assumes a utopia, thus failing to move society to reconciliation.